The Adsorption of Some Trace Heavy Metals from Aqueous Solution Using Non Living Biomass of Sub Merged Aquatic Plant Ceratophyllum demersum - A. Hassoon, Hassanein (Iraqi Journal of Science, 2023)
Heavy metals contamination in aquatic ecosystems is considered one of the most important threats of aquatic life. Submerge aquatic plants Ceratophyllum demersum in its non living form used for the removal of trace elements. This article studied the ability of the fine powder of C.demersum for the removal of some heavy metals (HM) like copper, cadmium, lead and chrome from aqueous solution with in variable experimental factors. The study occupy two treatments the first included different hydrogen ions pH within a range of 4, 5,6and 8 with a constant HM concentration (1000 ppm).While the second treatment represented by using variable HM concentrations within a range of (250,500,750and 1000 ppm) with a constant pH=7.In both treatments the amount of dried plant was 1g.According to analysis of variance the data obtained from this study revealed that removal efficiency of lead Pb reached to 99.9% where as the lower removal percentage % was for chrome Cr about 80%. Also the results indicated that C.demersum had high capabilities to remove trace elements, therefore it can be used for refining the waste water.